(untitled) (AYUSHDHARA, 2025)
Anxiety is a prevalent psychological disorder in contemporary society, often marked by excessive worry, restlessness, and feelings of fear. In the context of Ayurveda, this condition is known as Chittodvega, which signifies an imbalance within the mind and nervous system. This case study focuses on the Ayurvedic treatment of Chittodvega in a 35-year-old female who experienced ongoing anxiety. The therapeutic approach combined herbal remedies, dietary changes, lifestyle enhancements, and Panchakarma therapies. Important herbs used in the treatment included Ashwagandha, Brahmi, and Jatamansi, all aimed at balancing the Vata dosha identified as aggravated in the patient. Lifestyle changes promoted regular daily rhythms, stress-relief techniques such as yoga and meditation, and improved sleep hygiene. After six weeks of this treatment regimen, the patient noted considerable reductions in anxiety symptoms, leading to less worry, enhanced sleep quality, and improved emotional resilience. This case study underscores the effectiveness of Ayurvedic methods in addressing anxiety and offers valuable insights into holistic strategies for mental health. Future research is suggested to investigate the wider implications of Ayurveda in the field of mental health care.